Pengaruh Literasi Digital Keagamaan Terhadap Sikap Moderat Siswa Kelas Xi SMAN 1 Juwana - Moh Fachruddin Assidiqi; Ambarwati (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE INFLUENCE OF RELIGIOUS DIGITAL LITERACY ON MODERATE ATTITUDES OF GRADE XI STUDENTS OF SMA N 1 JUWANA This study aims to analyze the influence of religious digital literacy on the moderate attitudes of eleventh-grade students at SMA Negeri 1 Juwana. The development of information technology and digital media has affected the way students acquire religious knowledge, making good digital literacy skills necessary so that students are filter information critically and wisely. This study uses a quantitative approach with a survey method. The research population consisted of all eleventh-grade students, while the sample was determined using a random sampling technique. Data collection was carried out through the distribution of questionnaires regarding the level of religious digital literacy and students’ moderate attitudes. The data were analyzed using a simple linear regression test to determine the influence between the independent variable and the dependent variable. The results indicate that religious digital literacy has a positive and significant influence on students’ moderate attitudes. The higher the level of religious digital literacy possessed by students, the higher the moderate attitude reflected in behaviors of tolerance, openness, and the ability to appreciate differences. This study emphasizes the importance of strengthening religious digital literacy in the school environment as an effort to shape students’ moderate and adaptive character in the digital era.